In the light of dynamic competition: Should we make merger remedies more flexible? - Patrice Bougette; Oliver Budzinski; Frédéric Marty (Technische Universität Ilmenau, Institut für Volkswirtschaftslehre, 2023)
Mergers and acquisitions shape industry competition. Effective merger remedies are important for market efficiency and consumer welfare. This paper explores the need for more flexible remedies to address changing markets after mergers. While the EU permits some flexibility with less restrictive remedies, we conceptually advance the design elements of a dual-phase, bifurcated merger control system. This system integrates ex-ante processes with more systematic and comprehensive ex-post measures. Such an approach can address the shortcomings of the current system and, consequently, holds the potential to enhance merger control in dynamic markets.
Keywords: L41; K21; L13; 330; merger remedies; competition authorities; market dynamics; dynamic competition; oligopolies; innovation effects; European Union